Product Quality Improvement Through Training on Tempeh Packaging at PRIMKOPTI SWAKERTA Semanan - Anik Nur Habyba; Indah Permata Sari; Dorina Hetharia; Dedy Sugiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Packaging is the first thing seen in a product and today many companies are focused on developing product packaging designs to compete in the market. The improvements in the type and design of packaging can be done PRIMKOPTI SWAKERTA Semanan to maintain customer loyalty. The purpose of this dedication is to provide knowledge of more environmentally friendly packaging alternatives to support the sustainable development of the tempeh industry and its processing in Semanan. Devotional activities begin with an introductory survey and then continue with training conducted online with the devotional team and tempeh craftsmen. The delivery of several training materials was done in parallel related to quality improvement, some of these materials such as the application of Good Manufacturing Practice, maintenance of production machines and food packaging. The survey results showed that 66.7 % of craftsmen use clear plastic with a simple design and some do not even use labels. The remaining 33.3 % of tempeh craftsmen use a combination of aluminium foil and plastic packaging. Alternative solutions are provided in improving the quality of tempeh products through banana leaf packaging. Banana leaves help the process of fermentation on tempeh and also increase consumer interest in buying because it is preferred. Kraft paper packaging is recommended for use because it can reduce the risk of rancidity on tempeh chips and extend the shelf life. Semanan tempeh makers can use this food packaging alternative to attract back consumers' interest that decreased during the pandemic.